The Envelope Residues E152/156/158 of Zika Virus Influence the Early Stages of Virus Infection in Human Cells - Sandra Bos; Wildriss Viranaicken; Etienne Frumence; Ge Li; Philippe Desprès; Richard Y. Zhao; Gilles Gadea (Cells, 2019)
Emerging infections of mosquito-borne Zika virus (ZIKV) pose an increasing threat to human health, as documented over the recent years in South Pacific islands and the Americas in recent years. To better understand molecular mechanisms underlying the increase in human cases with severe pathologies, we recently demonstrated the functional roles of structural proteins capsid (C), pre-membrane (prM), and envelop (E) of ZIKV epidemic strains with the initiation of viral infection in human cells. Specifically, we found that the C-prM region contributes to permissiveness of human host cells to ZIKV infection and ZIKV-induced cytopathic effects, whereas the E protein is associated with viral attachment and early infection. In the present study, we further characterize ZIKV E proteins by investigating the roles of residues isoleucine 152 (Ile152), threonine 156 (Thr156), and histidine 158 (His158) (i.e., the E-152/156/158 residues), which surround a unique N-glycosylation site (E-154), in permissiveness of human host cells to epidemic ZIKV infection. For comparison purpose, we generated mutant molecular clones of epidemic BeH819015 (BR15) and historical MR766-NIID (MR766) strains that carry each other’s E-152/156/158 residues, respectively. We observed that the BR15 mutant containing the E-152/156/158 residues from MR766 was less infectious in A549-Dual™ cells than parental virus. In contrast, the MR766 mutant containing E-152/156/158 residues from BR15 displayed increased infectivity. The observed differences in infectivity were, however, not correlated with changes in viral binding onto host-cells or cellular responses to viral infection. Instead, the E-152/156/158 residues from BR15 were associated with an increased efficiency of viral membrane fusion inside infected cells due to conformational changes of E protein that enhance exposure of the fusion loop. Our data highlight an important contribution of E-152/156/158 residues to the early steps of ZIKV infection in human cells.